2009
DOI: 10.1037/a0016381
|View full text |Cite
|
Sign up to set email alerts
|

Parental depression and interparental conflict: Children and adolescents’ self-blame and coping responses.

Abstract: The present study examined the role of children and adolescents’ perceptions of self-blame specific to interparental conflict and children and adolescents’ coping behaviors in the context of parental depression as predictors of internalizing and externalizing symptoms in a sample of 108 youth (age 9–15 years old) of parents with a history of depression. Higher levels of current depressive symptoms in parents were associated with higher levels of interparental conflict and higher levels of internalizing symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 17 publications
7
65
0
Order By: Relevance
“…This coping pattern included both active and emotion-focused coping strategies, and thereby differs from previous findings. The overall pattern in previous research is that problem-focused coping is usually related to better mental health, whereas emotion-focused coping is associated with increased problems (Fear et al, 2009;Frydenberg & Lewis, 2009;Penley, Tomaka, and Wiebe, 2002;Valiente et al, 2009). In addition to situational and sample dissimilarities, different distinctions of coping strategies in previous research might have influenced these discrepancies.…”
Section: Coping and Mental Healthmentioning
confidence: 98%
“…This coping pattern included both active and emotion-focused coping strategies, and thereby differs from previous findings. The overall pattern in previous research is that problem-focused coping is usually related to better mental health, whereas emotion-focused coping is associated with increased problems (Fear et al, 2009;Frydenberg & Lewis, 2009;Penley, Tomaka, and Wiebe, 2002;Valiente et al, 2009). In addition to situational and sample dissimilarities, different distinctions of coping strategies in previous research might have influenced these discrepancies.…”
Section: Coping and Mental Healthmentioning
confidence: 98%
“…Offspring of depressed parents are at heightened risk for developing psychopathology as compared to children of non-depressed parents (Beardslee, Gladstone, & O’Connor, 2011; Hammen & Brennan, 2003). Other investigations of offspring of depressed parents have found that secondary control coping partially mediated the relation between the specific stressor of parental depression and children’s depressive symptoms (Fear et al, 2009; Jaser et al, 2005; Langrock et al, 2002). Thus, offspring of depressed parents are not only exposed to high levels of adverse life events, but they also tend to lack skills for coping with these stressors.…”
mentioning
confidence: 94%
“…Although evidence exists of significant links between stress and coping, and between coping and psychopathology, most of these findings have come from cross-sectional studies (e.g., Fear et al, 2009; Jaser et al, 2005, 2007; Langrock et al, 2002; Wadsworth & Berger, 2006; Wadsworth, Raviv, Compas, & Connor-Smith, 2005). Few investigations have tested a mediation model in which the relation between stress and depression in children is accounted for by coping, using a prospective design across multiple time points.…”
mentioning
confidence: 99%
“…Most of the studies reveal a direct relationship between accommodative coping resources (or related strategies) and health outcomes, expressed by negative correlations between accommodative coping and internalizing, externalizing and somatic symptoms, or emotional and behavioural problems (Connor-Smith, Compas, Wadsworth, Thomsen, & Saltzman, 2000;Fear et al, 2009;Garnefski, Kraaij, & Spinhoven, 2001;Garnefski et al, 2007;Hampel & Petermann, 2006;Hsieh & Stright, 2012;A. H. Thomsen et al, 2002;Turner-Sack, Menna, & Setchell, 2012).…”
mentioning
confidence: 99%